Biochar enhanced Cd and Pb immobilization by sulfate-reducing bacterium isolated from acid mine drainage environment. (15th September 2022) - Wu, Zheng; Firmin, Kotchikpa Adekunle; Cheng, Meiling; Wu, Hui; Si, Youbin
Abstract: Sulfate reducing bacteria (SRB) is considered to be the most promising alternative biological treatment for immobilization of heavy metals due to its high efficiency and low cost. However, the mechanism underlying the biomineralization process has remained unclear. The strain used in this study was isolated from a nonferrous metal smelter, and it was immobilized on biochar to produce biochar inoculated bacterium(BIC); the Cd 2+ and Pb 2+ immobilization efficacy of BIC were investigated under differing reaction times, temperatures, pH, solid liquid ratios and heavy metal concentrations. Moreover, the BIC immobilization products were analyzed by a series of characterization techniques. The results indicated that the strain identified as Clostridium sulfidigenes HY-1 was found to exhibit high resistances to Cd 2+ and Pb 2+ . The immobilization efficiency of BIC was much better than that of separate strain HY-1 and biochar. Altogether, the optimal immobilization conditions of BIC were found to be 3 d, pH 8.0, 30 °C, biochar addition of 0.6 g/L, and initial Cd 2+ and Pb 2+ concentrations of 5 and 30 mg/L, respectively. Under these conditions, the immobilization efficiencies of Cd 2+ and Pb 2+ were 67.9%, 95.7%, respectively. In addition, the BIC immobilization products were analyzed by Fourier transform infrared spectrometer, scanning electron microscope, energy dispersive spectroscopy and further confirmed to be CdS and PbS by X-ray diffraction and X-ray photoelectron spectroscopy. The results showed that biochar could enhance the bacterial immobilization effect; strain HY-1 produced S 2− during sulfate reduction, which could accumulate and react with Cd 2+ and Pb 2+ to form metal sulfide precipitates, mainly in the form of CdS and PbS that were immobilized and removed. These results suggest that BIC shows promise as an efficient means of immobilizing Cd 2+ and Pb 2+ from acid mine drainage (AMD). Graphical abstract: Image 1 Highlights: Sulfate-reducing Clostridium sulfidigenes HY-1 was isolated from acid mine drainage environment. Biochar enhanced Cd and Pb immobilization by Clostridium sulfidigenes HY-1. CdS and PbS precipitation mediated by strain HY-1 is the main way of heavy metal immobilization.